1951
DOI: 10.2172/915051
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Fixation by Microorganisms

Abstract: The place occupied by the photosynthetic mechanism of energy conversion in the stream of biochemical evolution has been the subject of considerable speculation (van Niel, 1949;Blum, 1937). It is clear, however, that in order to establish such a place, a more or less definite notion of the nature of the entire evolutionary stream is necessary. In recent years the idea that the stream is flowing in the direction of the loss of synthetic biochemical abilities has gained a special prominence, particularly as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1957
1957
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 3 publications
2
13
0
Order By: Relevance
“…"['he results with the sea mussel indicate that the Embden-Meyerhof scheme does not operate the same as in vertebrates. This is in agreement with the observation of many authors that succinate rather than lactate is the major fermentation product of a number of micro-organisms, intestinal helminths and bivalves which depend on anaerobic metabolism for their supply of energy (Lynch & Calvin, 1952;Saz & Beuding, 1966;Simpson & Awapara, 1966;Hammen, 1969). Stokes & Awapara (1968) incubated under nitrogen the mantle of Rangia euneata, a brackish water bivalve, with randomly labeled 14C-glucose.…”
Section: Resultssupporting
confidence: 89%
“…"['he results with the sea mussel indicate that the Embden-Meyerhof scheme does not operate the same as in vertebrates. This is in agreement with the observation of many authors that succinate rather than lactate is the major fermentation product of a number of micro-organisms, intestinal helminths and bivalves which depend on anaerobic metabolism for their supply of energy (Lynch & Calvin, 1952;Saz & Beuding, 1966;Simpson & Awapara, 1966;Hammen, 1969). Stokes & Awapara (1968) incubated under nitrogen the mantle of Rangia euneata, a brackish water bivalve, with randomly labeled 14C-glucose.…”
Section: Resultssupporting
confidence: 89%
“…6 be correct, Soluble I should consist largely of intermediates in the conversion of acetate to carbohydrates, presumably Krebs cycle acids, the phosphorylated intermediates of glucose metabolism and oligosaccharides. In partial support of this theory, Lynch & Calvin (1952, 1953 found that, of the acetate methyl-carbon incorporated into ethanol-soluble materials during incubation for 12 min. in the dark, nearly 50 yo was in the form of phosphorylated intermediates, 4 yo in the form of ' dextrins ', and about 25 yo in the form of amino acids related to the Krebs cycle.…”
Section: Discussionmentioning
confidence: 96%
“…Lynch and Calvin (25) found that a considerable amount of radioactivity was incorporated into a water-soluble polysaceharide when Allomyces arbuscula was suspended in a labeled bicarbonate solution-indicating that this polysaccharide was metabolically active. It may serve as an endogenous substrate.…”
Section: Discussionmentioning
confidence: 99%